Measurement of "Tone" - A Technical Aspect (Journal of Informatics and Mathematical Sciences, 2010)
The purpose of this research work is to measure the Tone value. The recorded speech material consists of the extracted portion ò of a syllable kò- (from kòṛa: `horse') is used for measuring the momentum of the pitch in tone. A native speaker of Punjabi language from the Doab region (Punjab, India) has been selected for producing the word kòṛa: (the focus of this work is not on the sociolinguistic study of the data of the nativespeaker). On the basis of the simple graphical representation a formula has been applied for measuring the tone value of the language. This paper seeks to improve our competence regarding acoustic measurements of acoustic data through graphical representation.
Keywords: Maximum pitch value; Minimum pitch value; tone